Start with Trust: Shifting from Pandemic-Centered to Person-Centered Leadership - Jerod Quinn; Tammy McCoy; Traci Stromie (Academic Chairpersons Conference Proceedings, 2022)
How policies and procedures regarding online learning, faculty coaching, and institutional policy around COVID (and post-COVID) can create more equitable support across the university.
Keywords: Online; COVID; Coaching; Policy